(untitled) (CIPEEX, 2025)
The evaluation of vital signs, traditionally associated with the clinical environment, is equally crucial in aesthetic practice. The objective of this study was to reinforce the importance of measuring vital signs as a pillar of biosecurity and professional ethics, considering the growing use of technologies that can induce physiological responses in patients. To this end, a narrative review of the scientific literature was conducted on the PubMed, SciELO, and LILACS databases, focusing on the basic parameters of blood pressure, heart rate, respiratory rate, body temperature, and oxygen saturation. The research, conducted between 2023 and 2025, analyzed articles that address the importance of these indicators for decision-making in health and aesthetic contexts. The results obtained indicate that the correct and systematic measurement of vital signs allows for the identification of contraindications and reduces the risk of complications. For example, the detection of uncontrolled hypertension can lead a professional to postpone or modify a procedure. This practice also strengthens patient trust and elevates the standard of care. The monitoring of vital signs, which can be done with the help of technology, is a valuable screening tool that supports safe therapeutic decision-making. In conclusion, the inclusion of vital sign monitoring in the pre-procedure physical examination is indispensable to ensure safety and individualized care, supporting evidence-based interventions. This practice should not be optional but a standard of conduct for all professionals in the aesthetic field.